How does it affect service delivery under the National Health Insurance Scheme in Ghana? Health providers and insurance managers perspective on submission and reimbursement of claims - Akweongo, P.; ChatioID, S.T.; Owusu, R.; Tedisio, F.; Salari, P.; Aikins, M. (PLOS ONE, 2021)
Introduction In 2003, the Government of Ghana launched the National Health Insurance Scheme (NHIS) to enable all Ghanaian residents to have access to health services at the point of care without financial difficulty. However, the system has faced a number of challenges relating to delays in submission and reimbursement of claims. This study assessed views of stakeholders on claims submission, processing and re-imbursement under the NHIS and how that affected health service delivery in Ghana. Methods The study employed qualitative methods where in-depth interviews were conducted with stakeholders in three administrative regions in Ghana. Purposive sampling method was used to select health facilities and study participants for the interviews. QSR Nvivo 12 software was used to code the data into themes for thematic analysis. Results The results point to key barriers such as lack of qualified staff to process claims, unclear vetting procedure and the failure of National Health Insurance Scheme officers to draw the attention of health facility staff to resolve discrepancies on time. Participants perceived that lack of clarity, inaccurate data and the use of non-professional staff for NHIS claims vetting prolonged reimbursement of claims. This affected operations of credentialed health facilities including the provision of health services. It is perceived that unavailability of funds led to reuse of disposable medical supplies in health service delivery in credentialed health facilities. Stakeholders suggested that submission of genuine claims by health providers and regular monitoring of health facilities reduces errors on claims reports and delays in reimbursement of claims. Conclusion Long delays in claims reimbursement, perceived vetting discrepancies affect health service delivery. Thus, effective collaboration of all stakeholders is necessary in order to develop a long-term strategy to address the issue under the NHIS to improve health service delivery.
Research Article
Keywords: National Health Insurance Scheme; service delivery; health services